PPA1, an energy metabolism initiator, plays an important role in the progression of malignant tumors - Wang, Shuying; Wei, Jianmei; Li, Shunwei; Luo, Yuyin; Li, Yifei; Wang, Xianglin; Shen, Wenzhi; Luo, Dehong; Liu, Daishun (Frontiers in Oncology, 2022)
Inorganic pyrophosphatase (PPA1) encoded by PPA1 gene belongs to Soluble Pyrophosphatases (PPase) family and is expressed widely in various tissues of Homo sapiens, as well as significantly in a variety of malignancies. The hydrolysis of inorganic pyrophosphate (PPi) to produce orthophosphate (Pi) not only dissipates the negative effects of PPi accumulation, but the energy released by this process also serves as a substitute for ATP. PPA1 is highly expressed in a variety of tumors and is involved in proliferation, invasion, and metastasis during tumor development, through the JNK/p53, Wnt/β-catenin, and PI3K/AKT/GSK-3β signaling pathways. Because of its remarkable role in tumor development, PPA1 may serve as a biological target for adjuvant therapy of tumor malignancies. Further, PPA1 is a potential biomarker to predict survival in patients with cancer, where the assessment of its transcriptional regulation can provide an in-depth understanding. Herein, we describe the signaling pathways through which PPA1 regulates malignant tumor progression and provide new insights to establish PPA1 as a biomarker for tumor diagnosis.